PENGARUH METODE LATIHAN SIRKUITTERHADAP KEMAMPUAN LOMPAT JAUH GAYA JONGKOKSMK TEKNOLOGI RIAU - Ahmad Yani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
Based on the researcher’s observation on the field, it seems that the ability of students of SMK Teknologi Riau in long jump is still low, and many students don’t have good enough techniques of long jump itself, besides that, the training method that is used is not appropriate yet. The purpose of this research is to find out the effect of circuit training method towards the students’ long jump ability at SMK Teknologi Riau. This type of this research is Experimental using T-test, the population of this research in class XI of SMK Teknologi Riau consist of 11 male students. The result of data analysis shows that : (1) There are different of result of long jump ability in circuit method (Thitung = 4.75 > Ttabel = 1.812),. So that is why Thitung bigger than Ttable its mean there is significant effect in using circuit method towards Long Jump of SMK Teknologi Riau students.